1994
DOI: 10.1063/1.466755
|View full text |Cite
|
Sign up to set email alerts
|

The thermal stability and fragmentation of C60 molecule up to 2000 K on the milliseconds time scale

Abstract: A method of generating effusive molecular beams of C60 with vibrational temperatures up to 2000 K is presented. Direct measurement of the thermal stability and fragmentation kinetics of C60 in the range of 1100–1970 K, on the milliseconds time scale, provides thermal rate constants k(T)=10–300 s−1 (for T=1720–1970 K, respectively) and activation energy of E0=4.0±0.3 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…It might be possible that the decline in fullerene mass is due in part to fragmentation of the fullerene molecules in addition to consumption by soot. However, previous studies have shown that C 60 is thermally stable in inert gas up to 1720 K [123,124]. As the temperature in these experiments did not exceed 1300 K, it is unlikely that any unimolecular fragmentation occurred.…”
Section: Discussionmentioning
confidence: 84%
“…It might be possible that the decline in fullerene mass is due in part to fragmentation of the fullerene molecules in addition to consumption by soot. However, previous studies have shown that C 60 is thermally stable in inert gas up to 1720 K [123,124]. As the temperature in these experiments did not exceed 1300 K, it is unlikely that any unimolecular fragmentation occurred.…”
Section: Discussionmentioning
confidence: 84%
“…Resilience and fragmentation were measured for free molecules excited by excimer laser pulses [5], electron impacts [12,13] or via cluster-surface collision processes [1][2][3][4]. It was found that the energy threshold of fragmentation of C 60 in surface collision is higher than that from electron impacts and laser pulse excitement [1,5,12,13]. A collisional fragmentation threshold of about 45 eV was suggested [5].…”
Section: Introductionmentioning
confidence: 98%
“…This surprising effect stimulated studies of surface scattering mechanisms, both experimentally and by atomic scale computer simulations [5][6][7][8][9][10][11]. Resilience and fragmentation were measured for free molecules excited by excimer laser pulses [5], electron impacts [12,13] or via cluster-surface collision processes [1][2][3][4]. It was found that the energy threshold of fragmentation of C 60 in surface collision is higher than that from electron impacts and laser pulse excitement [1,5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…1. It consists of the Technion two stage effusive source for superhot C 60 [19][20][21][22][23][24] which is interfaced to the cluster molecular beam machine 18 at the research institute Rijnhuizen of the Stichting voor Fundamenteel Onderzoek der Materie ͑FOM͒. The beam of superhot C 60 can then be irradiated by the tunable IR radiation, emitted from FELIX.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21][22][23][24] While the superhot thermal source method can not access the very high internal excitation range above 20 eV, it is presently the only method that can provide a controlled and well defined deposition of essentially pure vibrational thermal energy into C 60 molecules with a well defined canonical distribution. The combination of the thermally tunable superhot C 60 source with the ability of FELIX to resonantly heat thus provides a unique opportunity to study the behavior of an ensemble of extremely vibrationally excited C 60 molecules ͑Ē th = 50-100 eV͒ in a well controlled way.…”
Section: Introductionmentioning
confidence: 99%